Factors influencing teenage pregnancy among dalit ethnic groups in Bharatpur Metropolitian city, Chitwan - Koirala, Subash; Poudel, Eak Narayan; Koirala, Arun; Shrestha, Niki (Journal of Chitwan Medical College, 2021)
Background: Teenage pregnancy refers to any pregnancy from a girl who is 10-19 years of age. This study aimed at accessing the factors influencing teenage pregnancy at first birth among the Dalit ethnic groups in Bharatpur Metropolitan City. Methods: A community based cross-sectional study using face-to-face interview method was carried out in Bharatpur Metropolitan City, Chitwan, Nepal. A total of 217 married Dalit women who had given birth to at least one child and who were less than 25 years of age during the survey were considered as a sample. The data was collected from October 1st 2020 to 31st December 2020. We used Pearsons Chi-square test and binary logistic regression analysis to assess the factors influencing teenage pregnancy among Dalit ethnic groups in Bharatpur Metropolitan city, Chitwan. Results: Among 217 married women of Dalit ethnic groups, there were 93(42.9%) married women who gave birth to their first child during teenage years and 124(57.1%) women gave first birth after crossing the teenage years. Results show that teenage pregnancy at first birth differ significantly with mother’s education level [Just Literate (OR = 5.88; CI = 2.53-13.69)], Husband’s education level [Just Literate (OR = 3.06; CI = 1.33-7.02)], Husband’s occupation [Unemployment (OR = 7.87; CI = 2.17-28.46)] and Husband’s age at marriage [ ≤ 20 (OR = 6.01 CI = 3.27-11.06)]. Conclusions: Carrying out advocacy against teenage marriage & teenage pregnancy as well as implementing comprehensive sexuality education and safe motherhood education targeted to Dalit ethnic groups is the need of the hour.